Tumor Cell "Slimming" Regulates Tumor Progression through PLCL1/UCP1‐Mediated Lipid Browning. Issue 10 (25th March 2019) - Xiong, Zhiyong; Xiao, Wen; Bao, Lin; Xiong, Wei; Xiao, Haibing; Qu, Yan; Yuan, Changfei; Ruan, Hailong; Cao, Qi; Wang, Keshan; Song, Zhengshuai; Wang, Cheng; et al.
Abstract: Emerging evidence has highlighted the important role of abnormal lipid accumulation in cancer development and progression, but the mechanism for this phenomenon remains unclear. Here, it is demonstrated that phospholipase C‐like 1/uncoupling protein 1 (PLCL1)/(UCP1)‐mediated lipid browning promotes tumor cell "slimming" and represses tumor progression. By screening three independent lipid metabolism‐related gene sets in clear cell renal cell carcinoma (ccRCC) and analyzing the TCGA database, it is found that PLCL1 predicted a poor prognosis and was downregulated in ccRCC. Restoration of PLCL1 expression in ccRCC cells significantly represses tumor progression and reduces abnormal lipid accumulation. Additionally, a phenomenon called tumor cell "slimming, " in which tumor cell volume is reduced and lipid droplets are transformed into tiny pieces, is observed. Further studies show that PLCL1 promotes tumor cell "slimming" and represses tumor progression through UCP1‐mediated lipid browning, which consumes lipids without producing ATP energy. Mechanistic investigations demonstrate that PLCL1 improves the protein stability of UCP1 by influencing the level of protein ubiquitination. Collectively, the data indicate that lipid browning mediated by PLCL1/UCP1 promotes tumor cell "slimming" and consumes abnormal lipid accumulation, which represses the progression of ccRCC. Tumor cell "slimming" offers a promising new concept and treatment modality against tumor development and progression. Abstract : Tumors are often accompanied by abnormal lipid metabolism . Lipid browning is a special way of lipid consumption. This study discovers the role of lipid browning in tumors. A phenomenon called tumor cell "slimming" is found by which PLCL1 promotes lipid browning through UCP1 to regress tumor progression. It provides a promising new concept for the treatment of tumors.